Effectiveness of risk minimization measures for valproate: a drug utilization study based on implementation of a risk minimization programme in Europe, analysis of data from the UK. (4th March 2022) - Ehlken, Birgit; Nishikawa, Chihiro; Kaplan, Sigal; Dresco, Isabelle; Granados, Denis; Toussi, Massoud
Abstract: Objective: Since 2014, valproate has not been recommended for use in girls and women of childbearing potential unless other treatments are ineffective or not tolerated. Risk minimization measures (RMMs) of valproate were implemented to reduce the potential risks of developmental disorders among pregnant women. A drug utilization study was carried out to assess the effectiveness of RMMs. Methods: This was a multinational, non-interventional cohort study. For the UK, existing data from the Clinical Practice Research Datalink database were used. The primary study endpoint was a change in the proportion of valproate initiations preceded by other medications relevant for valproate indications before and after implementation of RMMs. Results: The proportion of valproate initiations preceded by medications related to valproate indications increased after RMM implementation in incident female users in the UK from 66.4% to 72.4%. The proportion of incident prescriptions for epilepsy and bipolar disorder with prior medication related to valproate indications increased, from 36.2% to 44.1% and 72.9% to 77.8%, respectively. The incidence rate of valproate-exposed pregnancies decreased from 16.9 to 10.9 per 1000 person-years in the pre- and post-implementation periods, respectively. Conclusions: Results from this study indicated some improvement in physician prescribing and a potential reduction in valproate-exposed pregnancies in the UK. Given only modest improvement has been achieved, additional RMMs were implemented in 2018.